The Nursing and Respiratory Behaviour of The Bottlenose Dolphin Calf (Tursiops aduncus) in Captive Breeding - Setiadi, Dedi Rahmat; Hastuti, Yohana Tri; Amani, Aqila Zata; Laksono, Mohamad Nanang Tejo; Manansang, Jansen; Mulia, Bongot Huaso; Manansang, Willem; Arifiantini, Raden Iis (Universitas Djuanda, 2025)
Bottlenose dolphins were often found in zoos and aquariums. Dolphin calves have a higher mortality rate in the first month after birth as they are unable to eat and breathe properly. The inability to thrive can affect growth until adulthood. This research was being conducted to better understand the nursing and breathing patterns of a bottlenose dolphin calf. Data were collected by observing the behaviour of a post-partum dolphin calf for 24 hours over 3 months (90 days). The behaviours observed were the calf's nursing (frequency, daily duration, and duration of suckling) and breathing (frequency). The results showed a decrease in the frequency of suckling and an increase in the duration of suckling, which indicated that the calf was becoming more successful at suckling. A constant decrease in respiratory frequency indicated a healthy growing calf due to an increase in lung capacity. These results indicated that the feeding and respiratory behaviour patterns of normally developing bottlenose dolphin calves showed a decrease in feeding frequency and an increase in feeding duration, as well as a decrease in respiratory frequency per week. Further studies on the feeding and respiratory behaviour of bottlenose dolphin calves.